Model and application of inversion data cleaning for flow monitoring stations in the middle route of the South-to-North Water Diversion Project - Ren, Honglei; Tao, Yuezan; Wei, Ting; Kang, Bo; Zhang, Naifeng; Li, Yucheng; Lin, Fei (Frontiers in Physics, 2023)
For a long-distance open-channel water transfer project, the correctness of hydrological state study and hydrodynamic numerical simulation is impacted directly by the spatiotemporal and consistency of the flow monitoring data along the project. Reported here is an inverted data cleaning model for flow monitoring stations based on the principle of water dynamic balance and the longest sequence method of interval flow, targeting the abnormal phenomenon of unequal flow at monitoring stations in the dispatching operation and using the middle route of the South-to-North Water Diversion Project in China as the research object. As an example, a hydrodynamic model is built for verification using flow and water level data after model cleaning as the upper and lower boundaries for the middle-route project from Baihe River to Huangjin River. The findings indicate that the cleaning model enhances the accuracy of flow monitoring data and reduces both the mean absolute error of the water level in front of the gate and the root mean square error by 0.0757m and 0.0895m, respectively. In terms of data spatial consistency and logic, the cleaned flow data is superior to measured flow data.